Comparative Analysis of Sustainable Food Governance and the Alignment of Food Security Policies to Sustainable Development: A Case Study of OIC Countries - Dalal Aassouli (16960260) (2023)
Employing Grey Relation Analysis (GRA) and Leximetrics, this study conducts a comparative analysis of sustainable food governance performance in the Organization of Islamic Cooperation countries (OIC). It assesses the alignment of their food security policies with sustainable development principles. Addressing a gap in the existing literature, the study aims to assess two separate components of food security governance, i.e., policy formulation and policy implementation. This is achieved by focusing on critical intrinsic factors like sustainable agriculture, sufficiency, resilience, and inclusivity, and sustainable finance which are often overlooked in policy formulation and evaluation. The findings reveal inadequate incorporation of sustainable finance, sustainable agriculture, circular food systems, and effective governance principles. Several countries lack concise policies (e.g., Iran, Turkmenistan, Suriname), relying on fragmented approaches, while others adopt regional food security strategies with observed differences in food governance versus policy alignment performance. The study enhances our understanding of food security governance and policy formulation and implementation, offering insights for advancing sustainability in the food security policies of the OIC. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su152215789